Translation of nonpolyadenylylated messenger RNA of sea urchin embryos. - Fromson, D (1976)
A large proportion of newly synthesized polyribosomal RNA of sea urchin blastulae is not polyadenylylated. The size distributions of the polyadenylylated and nonpolyadenylylated RNA are indistinguishable (mean size of 26 S). Upon translation of sea urchin polyribosomal RNA containing poly(A) and that without poly(A) in a wheat embryo cell-free protein-synthesizing system, where polypeptide synthesis is dependent on added messenger, both classes of RNA support peptide synthesis to the same extent. A preliminary analysis of the proteins synthesized in response to added mRNA (polyadenylylated and nonpolyadenylylated) indicates that these classes of mRNA molecules may code for different populations of proteins.